2022
DOI: 10.1002/ajh.26764
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic cell transplantation in patients with chronic phase chronic myeloid leukemia in the era of third generation tyrosine kinase inhibitors: A retrospective study by the chronic malignancies working party of the EBMT

Abstract: Following the introduction of tyrosine kinase inhibitors (TKI), the number of patients undergoing allogeneic hematopoietic cell transplantation (allo‐HCT) for chronic phase (CP) chronic myeloid leukemia (CML) has dramatically decreased. Imatinib was the first TKI introduced to the clinical arena, predominantly utilized in the first line setting. In cases of insufficient response, resistance, or intolerance, CML patients can subsequently be treated with either a second or third generation TKI. Between 2006 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
(40 reference statements)
1
6
0
1
Order By: Relevance
“…established[29], and as in that study, we also found that CP1 remains a major prognostic factor. Compared to AdP-CML, CP1-CML is associated less frequently with additional chromosomal abnormalities, kinase domain BCR::ABL1 point mutations, or somatic cancer gene mutations, which have been linked to worse outcomes [30À32].…”
supporting
confidence: 87%
“…established[29], and as in that study, we also found that CP1 remains a major prognostic factor. Compared to AdP-CML, CP1-CML is associated less frequently with additional chromosomal abnormalities, kinase domain BCR::ABL1 point mutations, or somatic cancer gene mutations, which have been linked to worse outcomes [30À32].…”
supporting
confidence: 87%
“…(29) Higher risk of mortality after allogeneic HCT among recipients with CML is reported for recipients of HCT at >1CP with observed >20% decreased survival, and with BCR-ABL1 mutations. (30,31) Strategies to predict TKI treatment resistance and optimal timing consideration for allogeneic HCT for young patients with CML-CP who manifest resistance to multiple TKI therapies should be followed as proposed in the ELN recommendations. (32) Donor/stem cell sources that contributed to improved access to allogeneic HCT showed different trends in each WHO region, but all regions were marked by an increase in the percentage of HCT from other related donors, the majority of whom were haploidentical donors.…”
Section: Discussionmentioning
confidence: 99%
“…2 Times have changed, and the spectacular success of tyrosine kinase inhibitors has predictably and rightly consigned allogeneic transplant to the back burners of CML therapy. In this issue of the American Journal of Hematology, Chalandon et al 3 provide a retrospective analysis of nearly 1000 CML undergoing allogeneic transplant across many centers belonging to the European CML consortium. There are always limitations that come with such studies (selection bias of patients actually analyzed, not accounting for center-to-center differences in outcomes, etc.…”
Section: Whither Transplantation For Cml?mentioning
confidence: 99%